1990
DOI: 10.1002/jbmr.5650050414
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of an osteoclast antigen and ruffled border on giant cells formed in response to resorbable substrates

Abstract: The osteoclast is the specialized multinucleated cell primarily responsible for the degradation of the organic and inorganic components of bone matrix. The functional and developmental relationship between osteoclasts and foreign body giant cells is unclear. The osteoclast plasma membrane ruffled border juxtaposed to the bone surface is a unique morphologic characteristic of active osteoclasts. In the studies reported here giant cell formation was induced in response to a variety of materials implanted onto th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
32
0

Year Published

1991
1991
1998
1998

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 25 publications
2
32
0
Order By: Relevance
“…Tissue response to implantation of mineralized materials seems to differ according to host species, receiving tissue and chemical composition of the implant, particularly the presence of bone proteins [36]. In this study, the results observed were similar in both types of biomaterials.…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…Tissue response to implantation of mineralized materials seems to differ according to host species, receiving tissue and chemical composition of the implant, particularly the presence of bone proteins [36]. In this study, the results observed were similar in both types of biomaterials.…”
Section: Discussionsupporting
confidence: 72%
“…It was demonstrated that chemical composition of the implanted material influences the degree of osteoclast differentiation. The formation of mineral matrix complexes by the adsorption to hydroxyapatite of bone extract or osteocalcin enhanced ruffled border formation and the presence of specific osteoclast antigen on elicited multinucleated cells [36]. When implanted subcutaneously, synthetic crystalline apatite was reported to generate multinucleated cells showing osteoclastic features, but only when associated with osteocalcin [40].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…It is, therefore, of interest to examine the ultrastructural features of the odontoclasts that resorb enamel in order to clarify the cellular mechanism of resorption of this unique and highly mineralized substrate. Furthermore, from the view point of the interaction between clastic cells and resorbed substrates, it is also interesting to study the odontoclasts that resorb enamel, because it has been considered that some of the organic components of nonenamel mineralized substrates, which are completely lacking in enamel matrix, may be responsible for the chemotaxis (Malone et al, 1982;Mundy and Poser, 1983;Lian et al, 1984), attachment (Reinholt et al, 1990;Miyauchi et al, 1993;Ross et al, 1993), and differentiation (Krukowski and Kahn, 1982;Glowacki and Lian, 1987;Webber et al, 1990) of clastic cells.…”
mentioning
confidence: 98%